True Grid: Three Case Studies of Moral Accounting. Issue 2 (1st June 2020) - Maas, Harro
Abstract: This article examines and compares three grids that were designed to serve explicit moral accounting goals: the calculation and improvement of character. The examples are tables which fall under a broad definition of diagrams. The examples follow another in time, but it is not the article's intention to suggest a historical lineage between them. Rather, it is the intention to clarify the interplay between grids and the precepts or keys to their use. The first case is the so-called ledger of merit and demerit that was propagated by Yuan Huang, a scholar and bureaucrat of the late Ming-period, who recommended its use for moral improvement in four letters to his son, of which the most famous letter was on the improvement of one's own fate. The second is Benjamin Franklin's Art of Virtue, which Franklin in his autobiographical letter to his son equally described as a tool of moral improvement. The third is the so-called moral thermometer, or biometer, a tool developed by the French revolutionary and pedagogical innovator Marc-Antoine Jullien, who described this tool as a moral mirror and compass that would be especially of use in preparing and educating adolescents for their adult lives. All three represent generic methods of producing knowledge about an individual's (moral) character, knowledge on which the users of these tables could act. Their differences have to do with the perceived relation of moral conduct to other spheres of life, religious, social, and economic, or all of these combined, but also with the different precepts to their use.